Deteksi Bakteri Pseudomonas cichorii Terbawa Benih Sawi Putih Impor Asal Korea Selatan dengan Metode PCR: Detection of Pseudomonas cichorii Bacteria Carried by Chinese Cabbage Seeds From South Korea Using PCR Method - Zahra, Nabila; Lestari, Safira Rizka (Agrocentrum, 2024)
Chinese cabbage (Brassica pekinensis L.) is one of the horticultural commodities that has a high production level in Indonesia. The increase in chinese cabbage production means that the need for chinese cabbage seeds in Indonesia is met through imported. The entry of seeds into a country through imported activities has the potential to as carriers of pathogens, especially bacteria that are OPTK A1 and A2, so it is important to carry out early detection of pathogens to prevent their spread in Indonesia. This research aims to detect bacteria carried by chinese cabbage seeds from South Korea using the PCR (Polymerase Chain Reaction) method. The results of the observations did not find the target bacteria Pseudomonas cichorii.